Global value chains - A Panacea for development? - Petra Dünhaupt; Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
In the last decades in particular, national governments as well as development agencies and international organizations have increasingly turned to participation in global value chains (GVCs) as a development strategy. However, whether the positive development effects of integration are large enough to warrant trade liberalization cannot be answered in a straightforward manner. In this article, we show how development recommendations by international institutions and Western governments have changed since World War II and now ultimately recommend integration into GVCs. Deregulation and liberalization of international trade and capital flows have fueled two opposing trends, which also affect GVCs: on the one hand, there is increasing concentration at the corporate level. On the other hand, globalization has resulted in more countries participating in international trade including via industrial production. Both developments have led to multinationals being able to expand their rent-seeking opportunities while also reducing production costs, especially for simple manufactured goods. Today, it is no longer sufficient for a country to industrialize in order to catch up with the rest of the world, as the prices for industrial goods and quality of productions have fallen tremendously in some cases, at least in comparison to developed countries. Integration into GVCs seems to provide only minimal macroeconomic benefits beyond the positive effects for individual companies and sectors. Industrial policy therefore seems indispensable for catch-up development.
Keywords: B27; F13; F63; 330; Global Value Chains; economic development; industrial policy; export market share concentration; import price development